2016
DOI: 10.5888/pcd13.160163
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Food and Beverage Marketing Policies and Practices in US School Districts, by Demographic Characteristics of School Districts, 2012

Abstract: IntroductionFoods and beverages marketed in schools are typically of poor nutritional value. School districts may adopt policies and practices to restrict marketing of unhealthful foods and to promote healthful choices. Students’ exposure to marketing practices differ by school demographics, but these differences have not yet been examined by district characteristics.MethodsWe analyzed data from the 2012 School Health Policies and Practices Study to examine how food and beverage marketing and promotion policie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…However, fewer resources exist to help districts address marketing of unhealthy foods and beverages, and states potentially are focusing assistance efforts on districts that are not already restricting marketing of unhealthy foods and beverages. Our findings were similar to previous findings (1) that, compared with large districts, small districts had lower odds of implementing several key marketing and promotion policies and practices.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, fewer resources exist to help districts address marketing of unhealthy foods and beverages, and states potentially are focusing assistance efforts on districts that are not already restricting marketing of unhealthy foods and beverages. Our findings were similar to previous findings (1) that, compared with large districts, small districts had lower odds of implementing several key marketing and promotion policies and practices.…”
Section: Discussionsupporting
confidence: 92%
“…Future studies could examine these associations with state- and district-level data that more closely align as well as examine associations between state-level food and beverage marketing policies and school-level practices, because state policies have been important levers for other school nutrition changes (9,10). Future research could also try to identify other training and technical assistance topics that may help districts address food marketing, including identifying food and beverage marketing in the school setting and leveraging school wellness councils to address food marketing (1). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…School characteristics, including district size, free/reduced lunch percentage and year of last policy revision were chosen prior to analysis based on the extant research. District size was categorized as small enrollment (1‐2499 students), medium enrollment (2500‐9999 students), and large enrollment (≥10,000 students) using previously established guidelines . Data on district‐level student enrollment for the 2015‐2016 school year were derived from publicly available enrollment data from the Wisconsin Department of Public Instruction (DPI).…”
Section: Methodsmentioning
confidence: 99%
“…The quality of SWPs, namely the inclusion of a comprehensive set of health promotion practices and the strength of policy language, appears to vary by several school district characteristics. District size is often associated with policy quality, although results remain equivocal as to whether larger or smaller districts have stronger policies . Studies suggest stronger policies are found in districts with a higher percentage of students receiving free or reduced lunch, and policy quality appears to be associated with student body mass index in districts with a majority of low‐income students .…”
mentioning
confidence: 99%